Evaluation of body heating protocols with graphene heated clothing in a cold environment. Issue 6 (30th November 2017) - Shin, Sora; Choi, Hae-Hyun; Kim, Yung Bin; Hong, Byung-Hee; Lee, Joo-Young
Abstract : Purpose: The purpose of this paper is to evaluate the effects of intermittent and continuous heating protocols using graphene-heated clothing and identify more effective body region for heating in a cold environment. Design/methodology/approach: Eight males participated in five experimental conditions at an air temperature of 0.6°C with 40 percent relative humidity: no heating, continuous heating the chest, continuous heating the back, intermittent heating the chest, and intermittent heating the back. Findings: The results showed that the electric power consumption of the intermittent heating protocol (2.49 W) was conserved by 71 percent compared to the continuous protocol (8.58 W). Rectal temperature, cardiovascular and respiratory responses showed no significant differences among the four heating conditions, while heating the back showed more beneficial effects on skin temperatures than heating the chest. Originality/value: First of all, this study was the first report to evaluate cold protective clothing with graphene heaters. Second, the authors provided effective intermittent heating protocols in terms of reducing power consumption, which was able to be evaluated with the characteristics of fast-responsive graphene heaters. Third, an intermittent heating protocol on the back was recommended to keep a balance between saving electric power and minimizing thermal discomfort in cold environments.